Ursula Hemetek and Adelaida Reyes (eds.): Cultural Diversity in the Urban Area: Explorations in Urban Ethnomusicology.: Vienna: Institut für Musik und Darstellende Kunst Wien, 2007, 160 pp + 2 accompanying CD, ISBN 978-3-902153-03-6. - Jurková, Zuzana (Lidé města, 2007)
A review of the book by Ursula Hemetek and Adelaida Reyes.